Effect of fiscal and monetary policy on private investment in Vietnam - Tung, Le Thanh (Business: Theory and Practice, 2022)
This paper aims to identify the effect of fiscal and monetary policy on private investment in Vietnam, a transition economy having robust economic growth. The quantitative analyze process employs the Autoregressive Distributed Lag (ARDL) model with a quarterly database in 2004–2020. The bound test study indicates that there is a long-term cointegration relationship between the policy variables and private investment. In the long run, the estimated result shows that the government expenditure and money supply have positive and significant impacts on private investment, however, the exchange rate has a negative and significant impact on private investment. In the short run, government expenditure also has a significant positive impact on private investment in Vietnam, besides, the lag of the private investment variable has a positive and significant which shows the supporting impact on private investment on itself. The coefficients of the tax revenue are positive and insignificant in the estimated functions. Therefore, the evidence suggests that the government needs to increase its expenditure which helps improve private investment in Vietnam in the future.